2018
DOI: 10.1136/bmjopen-2018-023154
|View full text |Cite
|
Sign up to set email alerts
|

How do general practitioners and pharmacists experience antibiotic use in out-of-hours primary care? An exploratory qualitative interview study to inform a participatory action research project

Abstract: RationaleAntibiotics (ABs) are one of the most prescribed medications in out-of-hours (OOH) care in Belgium. Developing a better understanding of why ABs are prescribed in this setting is essential to improve prescribing habits.ObjectivesTo assess AB prescribing and dispensing challenges for general practitioners (GPs) and pharmacists in OOH primary care, and to identify context-specific elements that can help the implementation of behaviour change interventions to improve AB prescribing in this setting.Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Earlier studies of OOH care have suggested that compared to IH care there are lower adherence to antibiotic guidelines [ 6 , 7 ], a higher antibiotic prescribing rate [ 8 , 9 ], a higher rate of prescriptions for broad-spectrum antibiotics [ 8 ], and more antibiotic prescriptions during weekends than weekday evenings [ 10 ]. In a qualitative study from Belgium, the physicians reported that the threshold for prescribing antibiotics was lower during OOH, but the choice of antibiotics was the same [ 11 ]. A more recent Belgian OOH study showed a high antibiotic prescribing rate for all indications, a high rate of not using recommended antibiotics, and an overuse of quinolones [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies of OOH care have suggested that compared to IH care there are lower adherence to antibiotic guidelines [ 6 , 7 ], a higher antibiotic prescribing rate [ 8 , 9 ], a higher rate of prescriptions for broad-spectrum antibiotics [ 8 ], and more antibiotic prescriptions during weekends than weekday evenings [ 10 ]. In a qualitative study from Belgium, the physicians reported that the threshold for prescribing antibiotics was lower during OOH, but the choice of antibiotics was the same [ 11 ]. A more recent Belgian OOH study showed a high antibiotic prescribing rate for all indications, a high rate of not using recommended antibiotics, and an overuse of quinolones [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this review, our study demonstrates that discussing context-specific barriers for participation with the relevant stakeholders beforehand can lead to successful data collection. Specific for the OOH context is the high workload and the specific role GPs feel they have as a GP on call (Colliers, Coenen, Remmen, Philips, & Anthierens, 2018). There is time pressure in these consultations, they have to be quick and efficient.…”
Section: Discussionmentioning
confidence: 99%
“…), they see a different type of patients (unknown patients, vulnerable patients, other ethnicities, demanding patients, etc. ), they feel time pressured, and there is a lack of diagnostic tools or follow-up (Colliers et al, 2018;S. J. Williams et al, 2018).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Although our data were from the same population, it was from a later time period; reasons for a higher antibiotic prescription rate are unclear. Qualitative work has revealed that GPs have a lower threshold for prescribing OOH [19]. They raised concerns including safety, a lack of background knowledge about patients in an OOH GP setting and a lack of availability of diagnostics [19].…”
Section: Comparison With the Literaturementioning
confidence: 99%